Cinematic and Literary Representations of Africans and Afro-descendants in Contemporary Portugal: Conviviality and conflict on the margins - Fernando Arenas (Cadernos de Estudos Africanos)
This article offers an analysis of feature films and literary fiction related to sub-Saharan African immigrants and their descendants in contemporary Portugal. I investigate how this cultural production reflects the changing Portuguese nation, where the boundaries between postcolonial Portugal and its former African colonies, as well as the notions of what constitutes “being African” or “being European”, are being redefined.